2011
DOI: 10.1177/1049732311399781
|View full text |Cite
|
Sign up to set email alerts
|

Balance, Balancing, and Health

Abstract: In this article we explore the concept of balance in the context of health. We became interested in balance during a grounded theory study of lay conceptualizations of cancer risk, in which participants were concerned with having a good life, which relied heavily on balancing processes. This led us to the qualitative literature about balance in the context of health, which was large and in need of synthesis. We identified 170 relevant studies and used Thomas and Harden's technique of "thematic synthesis" to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…The extent to which the participants experienced balance was determined by how well the collective needs of colleagues and family members were met and how happy they perceived their families and workmates to be as a whole. This finding significantly extends the understanding of balance, as the concept is typically associated exclusively with a state of individual health and well-being (Hämmig & Bauer, 2009;Lipworth et al, 2011;Sheldon et al, 2010) or the fulfillment of role-related responsibilities from an objective point of view (Grzywacz & Carlson, 2007). Such conceptualizations do not facilitate a holistic understanding of balance because they overlook the importance of collective happiness to parents with young children.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The extent to which the participants experienced balance was determined by how well the collective needs of colleagues and family members were met and how happy they perceived their families and workmates to be as a whole. This finding significantly extends the understanding of balance, as the concept is typically associated exclusively with a state of individual health and well-being (Hämmig & Bauer, 2009;Lipworth et al, 2011;Sheldon et al, 2010) or the fulfillment of role-related responsibilities from an objective point of view (Grzywacz & Carlson, 2007). Such conceptualizations do not facilitate a holistic understanding of balance because they overlook the importance of collective happiness to parents with young children.…”
Section: Discussionmentioning
confidence: 67%
“…Others use related terms such as life balance, work-life balance, and occupational balance. Recently published reviews of the literature on balance consistently identified a lack of consensus on the definition of balance (Chang et al, 2010;Lipworth, Hooker, & Carter, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While an ontology of balance has been developed (Christiansen and Matuska, 2006;Lipworth et al, 2011;Wagman et al, 2011), this article aims to explore an area that has received less attention: how ideas, practices and techniques of balance affect peoples' experiences of cancer, particularly when they are engaged with modalities of self-health (MacArtney, 2015;Broom, 2009). …”
Section: Techniquesmentioning
confidence: 99%
“…In particular, Lipworth et al (2011) conducted an instructive conceptual meta-analysis of the use of balance in qualitative studies of healthcare to provide a typology of balance. Lipworth et al divided balance into four analytical typologies, including two mechanisms of balance (as a state or as a process) and two orientations (internalist and externalist).…”
Section: Modalities Of Balancementioning
confidence: 99%
“…Responsibility can be illustrated as a continuum, ranging from a low degree of responsibility, exemplified as ignoring demands for which one is expected to take responsibility, to a burden, exemplified as demands related to achievements, performance and relations to others (Landstedt et al, 2009). Adolescents strive to obtain balance in these social processes, according to Lipworth, Hooker, and Carter (2011), who argue that health and well-being involve a state of balance in life.…”
Section: Introductionmentioning
confidence: 99%